Exploring the experiences of nurses and physicians infected with COVID-19 - Maryam Moghimian; Kolsoum Farzi; Sedigheh Farzi; Azam Moladoost; Simin Safiri (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Health-care providers, including physicians and nurses, are vital resources of the health-care system, and their health is essential to ensure safe care and to control outbreaks in the community. The aim of this study was to explore the experiences of physicians and nurses infected with COVID-19. MATERIALS AND METHODS: This descriptive exploratory qualitative study was conducted in 2020. To conduct this study, 19 participants (5 physicians and 14 nurses) were selected using purposive sampling. Data were collected using semi-structured interviews. Data analysis was performed using conventional content analysis. RESULTS: Eight main categories of "Fear and anxiety," "Fighting against COVID-19," "Feeling abandoned during home quarantine period," "Denial of disease despite testing positive," "Recovery: the second opportunity," "Imposition of psychological burden after returning to work," "Promotion of the health professional perception," and "Promising supportive resources," as well as 21 subcategories, were extracted from the participants' experiences. CONCLUSION: The experiences of physicians and nurses with COVID-19 revealed that their perception of the profession and providing care had changed. This experience has highlighted the focus and effort to promote patient-centered care and interprofessional collaboration among them.